2017
DOI: 10.5001/omj.2017.90
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Growth Hormone on Final Height in Children with Idiopathic Short Stature: A UAE, Eastern Region Experience

Abstract: In our local population, GH has a positive effect on the short-term growth and FH of children with ISS to the same extent that has been observed in children with idiopathic GH deficiency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Evidence supporting the safety profile of GH therapy includes large registries comprising more than 600,000 patients-years of GH exposure, and long-term safety cohorts of adults who received GH therapy as children (22). Several studies have reported favorable outcomes of GH treatment in the Arabian Gulf region (23)(24)(25)(26). Despite this, only 60% of the respondents considered GH safe.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence supporting the safety profile of GH therapy includes large registries comprising more than 600,000 patients-years of GH exposure, and long-term safety cohorts of adults who received GH therapy as children (22). Several studies have reported favorable outcomes of GH treatment in the Arabian Gulf region (23)(24)(25)(26). Despite this, only 60% of the respondents considered GH safe.…”
Section: Discussionmentioning
confidence: 99%